Analisis Faktor Yang Mempengaruhi Tingkat Kelancaran Pengembalian Kredit (Studi Kasus Pada PT. BPR Kawan Malang) - Anggraeni Purwatiningsih; Irene Rani Pornamasari (University of Merdeka Malang, 2020)
This study aims to analyze the characteristics of the borrower, the size of the loan, the economic sector, length of business, cash flow, and credit guarantees on the rate of return on credit at BPR Kawan. This type of research is a case study using a qualitative descriptive approach. Methods of data collection by conducting interviews, documentation, and observation. The sample used in the study amounted to 50 respondents who were active debtors of the Kawan People's Credit Bank from August to December 2019. The sampling technique used a random sample. The results showed that not all variables have an effect on the smoothness of credit repayments. Of all the research variables that do not have an effect, including the variable character of the borrower, the size of the loan, the economic sector, and credit guarantee. Meanwhile, the factors that influence the smooth return of credit at PT. Bank Perkreditan Rakyat Kawan is the length of business and cash flow. Duration of business and cash flow has a positive influ- ence and relationship with the smooth return of credit. From the results of the regression coefficient of determination, it can be seen that R Square is 0.619. The amount of determination coefficient is 0.287 or equal to 61.9%. This figure means that 61.9% of smooth repayment of credit can be explained by variables of the borrower's character, loan size, economic sec- tor, length of business, cash flow, and credit guarantee, while the remaining 38.1% can be explained by causal factors other. DOI: 10.26905/ap.v6i2.5092